The perception of e-leadership competencies and employee job performance among employees in higher educational institutions in Malaysia - Mohd Tajuddin, Jaslina; Asas, Asmawati; Noh, F. M.; A.Manaf, Aini Maznina (UiTM Press, 2024)
This study explores the relationship between the perception of e-leadership competencies and employee job performance among employees (academics and non-academics) in higher educational institutions in Malaysia by using Fiedler Contingency Model of Leadership. Besides, this study also investigates the difference between the perception of e-leadership competencies among academics and non-academics. e-leadership competencies refer to the ability of leaders to utilize information communication technologies (ICTs), adopting them by adding value to people and organizations and having the ability to know how to use them. In this study, e-leadership competencies were measured based on three dimensions from Fiedler Contingency Model of Leadership: leader-member relations, task structure, and position power in a nationwide survey. A survey questionnaire was used as the instrument to solicit the perception of 154 higher educational institution employees. Results showed that there were positive and moderate relationships between the perception of e-leadership competencies and employee job performance for all three dimensions. Moreover, results also indicated that there was not statistically difference between the perception of e-leadership competencies among academics and non-academics